PREPARASI PARTIKEL MAGNETIK DARI PASIR BESI PANTAI BATANG KAPAS SUMATERA BARAT MENGGUNAKAN METODE BALL MILLING - Tahayati Ichsan; Salomo Salomo; Erwin Erwin; Usman Malik (Komunikasi Fisika Indonesia, 2018)
Preparation of micro magnetic particle and its magnetic propertis from iron sand beach of Batang Kapas west Sumatera using Ball Milling method has been done. Prior to the Ball Milling process, the samples were processed by iron sand separator (ISS) in order to separate between magnetic particles and non magnetic one. Next, the concentrates from ISS were crushed by Ball Milling method  as a function of time namely 20, 40, and 60 hours. For separation between magnetic particles and non magnetic one, then NdFeB magnet was utilized. The results showed that the magnetic degree of the sample is about 0,5%. Measurements of magnetic induction solenoids were carried out using a Magnetic Probe Pasco PS -2162 as a function of current (2, 4, 6, 8 and 10) A and a  functions of distance (1, 2, 3, 4, and 5) mm. Then the total magnetic induction of the solenoid (solenoid with sample core and concentrate) was measured as a function of an electric current for a fixed distance of 1 mm. The calculation results showed that magnetic susceptibility and mass susceptibility increase with Ball Milling time from (3376,400-7765,130). This value is within the interval of 46-80000 which is the interval of Ilmenite mineral (FeTiO3; Antiferromagnetik). The increase in magnetic susceptibility and mass susceptibility of samples processed by Ball Milling is thought to be due to the increasing number of magnetic particles in the sample.